Patent pledges : global perspectives on patent law's private ordering frontier - Contreras, Jorge L., 1966-; Jacob, Meredith; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
Patent holders are increasingly making voluntary, public commitments to limit the enforcement and other exploitation of their patents. The best-known form of patent pledge is the so-called FRAND commitment, in which a patent holder commits to license patents to manufacturers of standardized products on terms that are "fair, reasonable and non-discriminatory." Patent pledges have also been appearing in fields well beyond technical standard-setting, including open source software, green technology and the biosciences. This book explores the motivations, legal characteristics and policy goals of these increasingly popular private ordering tools. Jorge Contreras and Meredith Jacob bring together work by more than a dozen international experts who examine the phenomenon of patent pledges from a variety of perspectives and analytical frameworks. The book assesses patent pledges as mechanisms for facilitating platform promotion, open innovation, economic development and environmental sustainability. Legal practitioners who are involved in intellectual property licensing, litigation and business transactions will find this book a key resource, as will in-house lawyers and managers at firms engaged in technology development and standardization. It will also be a key reference for scholars in law, economics, business and political science.
Introduction -- Part I: Landscape of patent pledges -- 1. A patent pledge taxonomy / Jorge L. Contreras -- 2. Unilateral patent pledges - motivations and key principles / Duane R. Valz -- 3. Red hat, open source and patent pledges / Mark Bohannon -- 4. Patent sharing in biotechnology / Dov Greenbaum -- 5. Patent pledges in green technology / Bassem Awad -- 6. Making environmentally beneficial patents available through the eco-patent commons / Scott Schang -- Part II: Litigation involving patent pledges -- 7. Patent pledge enforcement theories / Jorge L. Contreras -- 8. Patent pledges at the U.S. international trade commission / Elizabeth I. Winston -- 9. Voluntary patent pledges: enforcement in Germany / Catharina Maracke and Axel Metzger -- Part III: Competition law and patent pledges around the world -- 10. Is patent reform via private ordering anticompetitive? an analysis of open patent agreements / Matthew W. Callahan and Jason M. Schultz -- 11. Enforcing patent pledges under EU law / Rafal Sikorski -- 12. Patent pledges and antitrust law in Brazil / Ricardo Sichel -- 13. Patent pledge enforcement in China / Elizabeth Xiao-Ru Wang -- 14. Patent pledges: Korean perspectives / Sang-Seung Yi and Yoonhee Kim -- Part IV: Patent pledges and innovation -- 15. The informational effects of patent pledges / Clark D. Asay -- 16. Open innovation and patent pledges / Mariateresa Maggiolino -- 17. The role of patent pledges in the cloud / Liza Vertinsky -- 18. Patent pledges and developing countries: the tryst with India's destiny / Tania Sebastian -- Part V: Patent pledges moving forward -- 19. How to make and keep a patent pledge / Timothy Simcoe -- 20. A registry for patent pledges / Jorge L. Contreras -- 21. Overcoming information asymmetry in patent pledge records / Nicole Shanahan -- 22. Best practices for making patent pledges / Meredith Jacob -- Index.
Contributors include: C. Asay, B. Awad, M. Bohannon, M. Callahan, J. Contreras, D. Greenbaum, M. Jacob, Y. Kim, M. Maggiolino, C. Maracke, A. Metzger, L. Montagnani, J. Schultz, S. Scott, T. Sebastian, N. Shanahan, R. Sichel, R. Sikorski, T. Simcoe, D. Valz, L. Vertinsky, E. Wang, E. Winston, S.-S. Yi
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: patentové právo; patent laws and legislation; e-knihy online; e-books online